SMEs innovation capabilities and export performance: an entrepreneurial orientation view - Ribau, Cláudia P.; Moreira, António C.; Raposo, Mário (Journal of Business Economics and Management, 2017)
Although there are several studies analysing how innovation capabilities influence export performance, this study aims to present the impact of a set of internal innovation capabilities on export performance of small and medium-sized firms (smes), with the mediating role of entrepreneurial orientation contingent upon the proactive or reactive behaviour of the firms to external stimuli. The study involves the analysis of 147 questionnaire‐based survey of managers from plastic manufacturing smes operating in Portugal that were subjected to a Partial Least Squares-Structural Equation Modelling (PLS-SEM) technique. The results show that proactive firms to external stimuli are not only better at innovating but also their entrepreneurial orientation capabilities underpin a better performance in international markets when compared with firms that react to external stimuli. This study has implications for smes aiming at increasing their export performance and innovativeness. For practitioners the findings of this study should enable smes owner/managers to better understand the possible impacts of innovation capabilities and entrepreneurial orientation on export performance, and thus lead to more effective smes management.